FACTORS INFLUENCING THE ADOPTION OF INTEGRATED SOIL FERTILITY MANAGEMENT TECHNOLOGIES BY SMALLHOLDER FARMERS IN NAMTUMBO DISTRICT, TANZANIA - Hija Walad Mwatawala; Estherbella Martin Burian (Big Data in Agriculture, 2024)
Sub-Saharan African smallholder farmers face two challenges: low production and restricted funding for nutrient inputs. By combining the use of enhanced germplasm, prudent fertiliser use, and organic matter management tailored to the local farming conditions, integrated soil fertility management seeks to increase productivity. This study set out to evaluate determinants for the adoption of integrated soil fertility management technologies by smallholder farmers in Namtumbo district, Tanzania. The design of the study was cross-sectional. Using the random sampling technique, 223 respondents were selected. The study utilised IBM SPSS to analyse both descriptive and inferential statistics. The findings show that almost all farmers adopted the ISFM initiative’s supported technologies, including better-quality seed strains, legume-maize rotation, and maize-legume intercropping. Findings on the determinants for the adoption ISFM knowledge were depicted by a binary logistic regression model whereby variables included in the model were good (Nagelkerke R2 = 0.81) predictors of determinants for adoption of ISFM technologies by farmers. Soil fertility, climatic conditions, education, participation in groups, access to extension services, cost of input and credit access had substantial (p< 0.05) influences on the probability of adoption of ISFM technology by a farmer. The inference of this discovery is that the adoption of ISFM technologies is affected by various factors. In order to guarantee accurate agricultural information on ISFM technologies and boost productivity, the study recommends increasing the number of extension staff and raising awareness among farmers about the importance of using extension staff. Adoption of ISFM procedures is also significantly influenced by the availability of better seed varieties. For this reason, smallholder farmers ought to have easier access to more inexpensive, better seed varieties. Furthermore, there should be a strong emphasis on intercropping maize and legumes as well as rotating legumes with maize.